The Earth BioGenome Project Phase II: illuminating the eukaryotic tree of life - Blaxter, Mark; Lewin, Harris A.; DiPalma, Federica; Challis, Richard; da Silva, Manuela; Durbin, Richard; Formenti, Giulio; Franz, Nico; Guigo, Roderic; Harrison, Peter W.; Hiller, Michael; Hoff, Katharina J.; et al. (Frontiers in Science, 2025)
The Earth BioGenome Project (EBP) aims to “sequence life for the future of life” by generating high-quality reference genome sequences for all recognized eukaryotic species, thereby building a rich knowledge base to inform conservation, inspire bioindustry, ensure food security, advance medicine, and establish a deeper understanding of biodiversity. As the EBP works toward completing the original Phase I goal—a reference genome for each of the approximately 10,000 taxonomic families of eukaryotes—milestone publications have demonstrated the transformative potential of the project. The EBP has promoted global collaboration and established core methods and standards. By the end of 2024, EBP-affiliated projects had publicly released 2,000 high-quality genome assemblies, representing more than 500 eukaryotic families. In this article, we present a revised set of goals for Phases I and II of the EBP. For Phase II, we propose generating reference genomes for 150,000 species over 4 years, including representative genomes for at least 50% of all accepted genera and for additional species of biological and economic importance. To deliver Phase II, EBP-affiliated projects will have to release over 3,000 new genomes per month. We review the magnitude of the tasks in sourcing, sequencing, assembling, annotating, and analyzing genomes at this scale, and explore the scientific, technical, social, legal, ethical, and funding challenges associated with them. Success in Phase II will set the stage for sequencing the remaining ~1.5 million named species of Eukaryota and establishing the knowledge platforms necessary for understanding, preserving, and utilizing Earth’s biodiversity in an era of rapid environmental change.